Neuroprotective effects of FK-506, L-carnitine and azathioprine on spinal cord ischemia-reperfusion injury - (:unkn) unknown (OXFORD UNIV PRESS INC, 2004)
Objective: In our experimental study, we aimed to test the effect of FK506, azathioprine and L-carnitine on protection of spinal cord injury due to ischemia-reperfusion. Methods: Twenty-seven Spraque-Dawley male rats were randomly divided into five groups. They were subjected to spinal cord ischemia by clamping the abdominal aorta for 45 min. Thirty minutes before the aortic clamping, group I received 0.5 mg/kg FK506, group II received 100 mg/kg L-carnitine, group III received 4 mg/kg azathioprine, the fourth group was the control group and received only normal saline injection intravenously and the last group was the sham group. Neurological status was scored by using the Tarlov scoring system. Sections of the lumbar cord were harvested for histopathological grades (1-4), having regard to percentage of the apoptotic cells. Results: Hind-limb motor function had recovered normally 48 h after the operation in all rats which received FK506, azathioprine and L-carnitine prophylactically. In contrast, all rats in the control group had deteriorated to paraplegia by 48 h after the operation (P < 0.05). Histopathologic sections in the involved spinal cord segment showed that a greater number of motor neuron cells were preserved and there were less apoptotic cells in the rats that received FK506, azathioprine and L-carnitine than those in control group. Conclusions: These results suggest that prophylactic use of FK506, azathioprine and L-carnitine protects motor neuron cells from ischemic spinal cord injury. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: ischemia/reperfusion; spinal cord; THORACOABDOMINAL AORTIC-SURGERY; L-PROPIONYL CARNITINE; THORACIC AORTA; FK506; HYPOTHERMIA; PREVENTION; PROTECTION; HEART